Costs of the Smoking Cessation Program in Brazil - Andréa Cristina Rosa Mendes; Cristiana Maria Toscano; Rosilene Marques de Souza Barcellos; Alvaro Luis Pereira Ribeiro; Jonas Bohn Ritzel; Valéria de Souza Cunha; Bruce Bartholow Duncan
ABSTRACT OBJECTIVE To assess the costs of the Smoking Cessation Program in the Brazilian Unified Health System and estimate the cost of its full implementation in a Brazilian municipality. METHODS The intensive behavioral therapy and treatment for smoking cessation includes consultations, cognitive-behavioral group therapy sessions, and use of medicines. The costs of care and management of the program were estimated using micro-costing methods. The full implementation of the program in the municipality of Goiania, Goias was set as its expansion to meet the demand of all smokers motivated to quit in the municipality that would seek care at Brazilian Unified Health System. We considered direct medical and non-medical costs: human resources, medicines, consumables, general expenses, transport, travels, events, and capital costs. We included costs of federal, state, and municipal levels. The perspective of the analysis was that from the Brazilian Unified Health System. Sensitivity analysis was performed by varying parameters concerning the amount of activities and resources used. Data sources included a sample of primary care health units, municipal and state secretariats of health, and the Brazilian Ministry of Health. The costs were estimated in Brazilian Real (R$) for the year of 2010. RESULTS The cost of the program in Goiania was R$429,079, with 78.0% regarding behavioral therapy and treatment of smoking. The cost per patient was R$534, and, per quitter, R$1,435. The full implementation of the program in the municipality of Goiania would generate a cost of R$20.28 million to attend 35,323 smokers. CONCLUSIONS The Smoking Cessation Program has good performance in terms of cost per patient that quit smoking. In view of the burden of smoking in Brazil, the treatment for smoking cessation must be considered as a priority in allocating health resources.